Transmembrane 163 (TMEM163) protein interacts with specific mammalian SLC30 zinc efflux transporter family members - Adrian Escobar; Daniel J. Styrpejko; Saima Ali; Math P. Cuajungco (Biochemistry and Biophysics Reports, 2022)
Recently, we reported that TMEM163 is a zinc efflux transporter that likely belongs to the mammalian solute carrier 30 (Slc30/ZnT) subfamily of the cation diffusion facilitator (CDF) protein superfamily. We hypothesized that human TMEM163 forms functional heterodimers with certain ZNT proteins based on their overlapping subcellular localization with TMEM163 and previous reports that some ZNT monomers interact with each other. In this study, we heterologously expressed individual constructs with a unique peptide tag containing TMEM163, ZNT1, ZNT2, ZNT3, and ZNT4 (negative control) or co-expressed TMEM163 with each ZNT in cultured cells for co-immunoprecipitation (co-IP) experiments. We also co-expressed TMEM163 with two different peptide tags as a positive co-IP control. Western blot analyses revealed that TMEM163 dimerizes with itself but that it also heterodimerizes with ZNT1, ZNT2, ZNT3, and ZNT4 proteins. Confocal microscopy revealed that TMEM163 and ZNT proteins partially co-localize in cells, suggesting that they exist as homodimers and heterodimers in their respective subcellular sites. Functional zinc flux assays using Fluozin-3 and Newport Green dyes show that TMEM163/ZNT heterodimers exhibit similar efflux function as TMEM163 homodimers. Cell surface biotinylation revealed that the plasma membrane localization of TMEM163 is not markedly influenced by ZNT co-expression. Overall, our results show that the interaction between TMEM163 and distinct ZNT proteins is physiologically relevant and that their heterodimerization may serve to increase the functional diversity of zinc effluxers within specific tissues or cell types.